International financial markets' influence on the welfare performance of alternative exchange rate regimes - Mathias Hoffmann (Deutsche Bundesbank, 2008)
In this paper Friedmann (1953) and Mundells (1968) position favouring flexible over alternative exchange rate regimes is reassessed in the context of international financial market integration. In a new open economy macroeconomic framework the paper shows that financial market integration causes a monetary policy trade-off between stabilising domestic goods prices as opposed to stabilising the terms of trade. Therefore, the welfare ranking of different exchanges rate rules changes during the process of international financial integration. It becomes evident that no single exchange rate regime outperforms in stabilising both domestic consumption and output variability in the process of financial market integration.
Keywords: F41; F36; F21; 330; International Financial Market Integration; Exchange Rate Rules; Optimal Monetary Policy; Welfare; Internationaler Finanzmarkt; Marktintegration; Wechselkurssystem; Wohlfahrtseffekt; Neue Makroökonomik offener Volkswirtschaften; Geldpolitik; Theorie